2019
DOI: 10.3389/fgene.2019.01159
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Use of Environmental DNA for the Non-Invasive Genotyping of a Bivalve Mollusk, the European Flat Oyster (Ostrea edulis)

Abstract: Accurate SNP (single nucleotide polymorphism) genotype information is critical for a wide range of selective breeding applications in aquaculture, including parentage assignment, marker-assisted, and genomic selection. However, the sampling of tissue for genetic analysis can be invasive for juvenile animals or taxa where sampling tissue is difficult or may cause mortality (e.g. bivalve mollusks). Here, we demonstrate a novel, non-invasive technique for sampling DNA based on the collection of environmental DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Cumulatively, these studies have demonstrated the value of DNA evidence for the management of NNS. Furthermore, observations from both laboratory [47,48] and field studies [49][50][51][52][53][54] have shown that eDNA can provide population genetics inference, but very little work has used this approach to study NNS [55].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, these studies have demonstrated the value of DNA evidence for the management of NNS. Furthermore, observations from both laboratory [47,48] and field studies [49][50][51][52][53][54] have shown that eDNA can provide population genetics inference, but very little work has used this approach to study NNS [55].…”
Section: Introductionmentioning
confidence: 99%
“…Given the low abundance of oysters in many locations, reaching this sample size can present a challenge in itself. eDNA analysis represents a potential opportunity to overcome these difficulties in sampling (Holman, Hollenbeck, Ashton, & Johnston, 2019; MĂ©rou, Lecadet, Pouvreau, & Arzul, 2020). In a hatchery setting, production of O. edulis spat is an ongoing challenge (LapĂšgue, Beaumont, Boudry, & Goulletquer, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Although frequency estimates can be derived for DNA pooled from archived samples or new collections, we ultimately expect the most efficient approach to quantifying contemporary allele-frequencies will be from environmental DNA samples. Conceptually similar eDNA genotyping assays have already been applied to diverse management needs, such as determining the proportion of conspecific carp derived from a non-native source ( Uchii, Doi & Minamoto, 2016 ), noninvasive genotyping of cultured oysters ( Holman et al, 2019 ), and noninvasive haplotyping of whale sharks ( Dugal et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%